2020
DOI: 10.1080/02640414.2020.1835236
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between perceived coach leadership and athletes’ affective states experienced during competition

Abstract: We examined whether coach leadership behaviours predicted intensity and direction of positive and negative affects experiencing during competition controlling for affects experienced within two hours before competition. 296 athletes (33% female and 67% male; Mage = 21.61; SD = 6.32) voluntarily participated in the study. A partial least square path modelling (PLS-PM) approach was used to examine the relationships between the study variables.The results showed that coach social support significant positively pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 37 publications
1
18
0
Order By: Relevance
“…The study carried out on the preference of the coach's leadership, among young Badminton athletes, revealed that the autocratic profile is the least requested (Cruz and Kim, 2017). The study by González-García et al (2020), carried out with young athletes of different collective and individual modalities, found significant associations between the autocratic profile and the emotions related to involvement unpleasant with the sport. The study by , carried out with adult athletes of different modalities, found significant associations between the combination of autocratic behavior, training and instruction, positive feedback and social support, with emotions related to happiness and seeking support.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The study carried out on the preference of the coach's leadership, among young Badminton athletes, revealed that the autocratic profile is the least requested (Cruz and Kim, 2017). The study by González-García et al (2020), carried out with young athletes of different collective and individual modalities, found significant associations between the autocratic profile and the emotions related to involvement unpleasant with the sport. The study by , carried out with adult athletes of different modalities, found significant associations between the combination of autocratic behavior, training and instruction, positive feedback and social support, with emotions related to happiness and seeking support.…”
Section: Discussionmentioning
confidence: 99%
“…Environments where young people establish a good quality relationship with coaches and perceive a sense of belonging are associated with greater personal and social development (Bruner et al, 2017;Vella et al, 2013). Coaches who provide social support to athletes generate positive effects of prospective adaptation when dealing with the emotions of competitive sports environments (González-García et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Conversely, negative experiences in this context can lead to early sport drop-out [4]. At this point, the figure of coaches may play a key role in the athlete's learning process, and can be a positive influence on the motivation and sport commitment of young soccer players [5][6][7].…”
Section: Introductionmentioning
confidence: 99%